Wastra Batik As A Fashion Interest Among Generation Z In The Community Of Remaja Nusantara (2023) - Adjani, Syifa Mahala (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research investigates the interest of Generation Z in batik textiles as a fashion element within the Nusantara Youth Community in Jakarta. Batik textiles are perceived not only as a fashion statement but also as a medium for expressing cultural identity. Generation Z, growing up in the digital era, integrates batik textiles with contemporary fashion trends. Each batik fabric possesses unique features and symbolism reflecting Indonesian culture. The Nusantara Youth Community, established in 2020, strives to preserve batik textiles through various activities and campaigns. The study employs an ethnographic approach, focusing on interactions within the community, revealing that Generation Z in Jakarta has a strong inclination towards batik textiles. The research aims to identify the aesthetic values driving their interest and to understand the effectiveness of the community's preservation campaigns. Findings indicate that Generation Z incorporates batik textiles into their fashion choices, influenced by both aesthetic appeal and cultural resonance. While the Nusantara Youth Community plays a role in this trend, a cultural understanding gap was identified that requires addressing. Overall, the research provides insights into the cultural fashion interests of Generation Z and the aspirations of the new generation towards cultural heritage.